2012
DOI: 10.1186/1471-2458-12-720
|View full text |Cite
|
Sign up to set email alerts
|

Women’s higher likelihood of disability pension: the role of health, family and work. A 5–7 years follow-up of the Hordaland Health Study

Abstract: BackgroundWomen’s higher risk of disability pension compared with men is found in countries with high female work participation and universal welfare schemes. The aim of the study was to examine the extent to which self-perceived health, family situation and work factors explain women’s higher risk of disability pension. We also explored how these factors influenced the gender difference across educational strata.MethodsThe population-based Hordaland Health Study (HUSK) was conducted in 1997–99 and included in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 40 publications
3
26
0
Order By: Relevance
“…In contrast to that study, we found the demographic factors of older age and shorter education to be significantly associated with DP. As in studies of the general female population, our study of LSCCs replicated short education, poor self-rated health, comorbidity, and increased levels of mental distress as factors associated with holding DP [4,21]. We also confirmed the relevance of somatic comorbidities reported in previous registry studies of DP among female breast cancer survivors [22,23].…”
Section: Discussionsupporting
confidence: 86%
“…In contrast to that study, we found the demographic factors of older age and shorter education to be significantly associated with DP. As in studies of the general female population, our study of LSCCs replicated short education, poor self-rated health, comorbidity, and increased levels of mental distress as factors associated with holding DP [4,21]. We also confirmed the relevance of somatic comorbidities reported in previous registry studies of DP among female breast cancer survivors [22,23].…”
Section: Discussionsupporting
confidence: 86%
“…Self-perceived health was evaluated in 12 studies,7–9 23 24 26 30 36 37 43 46 48 presenting 13 associations. In all 12 studies self-perceived poor health was a significant risk factor for transition into disability pension (table 1) with a pooled RR of 3.61 (95% CI 2.44 to 5.35), table 2 and figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…Poor health was measured on a 5-point Likert scale,7–9 26 43 46 a 4-point Likert scale23 24 48 or with the short-form health survey (SF-12 or SF-36) 30 36. In eight studies poor health was defined as ‘less than good health’,7–9 24 30 43 46 48 whereas the other studies defined poor health as ‘less than fair health’,23 ‘less than moderate health’26 or as a cut-off value <40 on the SF-36 36. Explorative analysis showed no influence of different cut-off values on pooled estimates of self-perceived poor health (‘less than good health’: RR 3.08, 95% CI 1.94 to 4.88; ‘less than fair/moderate health’: RR 4.07, 95% CI 1.70 to 9.71).…”
Section: Resultsmentioning
confidence: 99%
“…In the Oslo Health study, the higher rates of DP among women were attributable to self-reported health, level of mental distress, working conditions, and income [34]. This is in contrast to the population-based study in Hordaland (HUSK), where self-perceived health, work factors and family situation did not explain women’s higher likelihood of DP [17]. Thus, results seem to differ between populations and studies and there is still no consensus in how to understand the gender divide in sick leave and DP.…”
Section: Discussionmentioning
confidence: 99%
“…Norwegian women have a higher rate of sick leave and DP than men, and still little is known on this gender divide [16, 17]. Female gender [1, 4, 18] and higher age [1, 19, 20] predict lack of RTW.…”
Section: Introductionmentioning
confidence: 99%